Integrating AI Chatbots into ESL Speaking Practice: A Study on Learner Autonomy in Jakarta - Alexia Mavrommatis; Felipe Souza; Rafaela Lima (International Journal of Language and Ubiquitous Learning, 2025)
Background. Artificial Intelligence (AI) chatbots have emerged as transformative tools in English as a Second Language (ESL) instruction, particularly for enhancing speaking skills through interactive, learner-centered engagement. Purpose. The research aims to identify the extent to which chatbot-based interaction fosters independent language learning, self-regulation, and communicative confidence. Employing a mixed-method design, data were collected from 80 undergraduate ESL learners through pre- and post-speaking assessments, learner autonomy questionnaires, and semi-structured interviews.   Method. Quantitative data were analyzed using paired-sample t-tests to measure improvements in speaking fluency and autonomy, while qualitative responses provided deeper insights into learners’ perceptions and experiences. Results. Results indicated significant gains in both speaking performance (p < .05) and self-directed learning behaviors, with participants reporting increased confidence, flexibility, and willingness to practice without instructor supervision. Qualitative findings further revealed that AI chatbots, perceived as nonjudgmental interlocutors, reduced learners’ speaking anxiety and encouraged spontaneous communication. Conclusion. The study concludes that integrating AI chatbots into ESL speaking activities effectively promotes learner autonomy and oral proficiency. These findings underscore the pedagogical potential of AI technology to foster independent, interactive, and confidence-building learning experiences in Indonesian ESL contexts.